Digestibility of protein and estimated bioavailability of mineral compounds in plant-based yoghurt alternatives - Anastassia Zeinatulina; Kristel Tanilas; Kristel Ehala-Aleksejev; Ene Viiard; Tiina Kriščiunaite (Future Foods)
This study evaluated the nutritional quality of 25 commercial plant-based (PB) yoghurt alternatives (lupin-, soya-, oat-, coconut-based), focusing on protein digestibility and amino acid score and the content of the essential minerals calcium, iron, magnesium, and zinc. The phytates levels were also measured to estimate mineral bioavailability. The content of saponins was examined in soya and oat products. The findings of this study revealed a high variability of Protein Digestibility-Corrected Amino Acid Score (PDCAAS) within product groups, with values ranging from 0.21 to 0.82 for soya-based yoghurt alternatives and from 0.41 to 1.00 for oat-based yoghurt alternatives. Only one oat product exhibited high-quality protein (PDCAAS > 0.9). Most products had low mineral content, which makes them unsuitable as a mineral source. Phytates hindered the low mineral content, with levels ranging from 13 to 193 mg/100 g. However, products enriched with calcium showed satisfactory levels, and phytate content had minimal impact on the estimated calcium bioavailability. Oat- and soya-based products contained 1–8 mg/100 g of avenacosides and 11–18 mg/100 g soyasaponins, respectively. This research underscores the importance of paying more attention to the nutritional value during product development of PB yoghurt alternatives manufactured using various constituents and when incorporating these products into dairy-free diets.